Dinamika Resiliensi Korban Perceraian Orang Tua - Widya Nugraha, Andreas Corsini; Mic Finanto Ario Bangun; Budi Sarasati; Chardelia Penggalih; Cinta Perindu (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
This research aims to determine the dynamics of psychological resilience in adolescent victims of parental divorce. The research used 1 subject, each of whom experienced their parents' divorce. The approach used in this research is quantitative phenomenology to obtain in-depth data regarding the dynamics of resilience experienced by the subject. The dynamics of resilience built by the subject are behavioral control and emotional balance.